Anti-Inflammatory properties of Salograviolide A purified from Lebanese plant Centaurea ainetensis - Saliba Najat A; Salloum Ralph; Al-Ashi Randa; Al-Saghir Jamal; Talhouk Rabih S; Homaidan Fadia R (BMC, 2009)
Abstract Background Anti-inflammatory activities of medicinal plants have largely been attributed to their content of sesquiterpene lactones (SLs). SLs are predominantly found in the sunflower family Asteraceae and have been isolated from many plants of this family, particularly Centaurea. The anti-inflammatory activities of extract of Centaurea ainetensis, a Lebanese endemic plant, and the isolated active molecule were assessed for their potential ant-inflammatory activities. Methods Plant extract from Centaurea ainetensis, and the isolated active ingredient Salograviolide A (SA), a sesquiterpene lactones guaianolide, were used for the study. Western blotting and electrophoretic mobility shift assays were used to test the effects of the plant extract and SA on interleukin-1 (IL-1) induced increase in cyclooxygenase-2 (COX-2) levels and in nuclear factor-κB (NF-κB) translocation in an intestinal epithelial cell (IEC) of inflammation. Their effects on inflammation score and cytokine levels were also studied in an iodoacetoamide-induced rat model of inflammation. Results Plant extract and SA were shown to reverse the effects observed by IL-1 on COX-2 levels and NF-κB translocation in IEC. SA decreased the level of inflammatory cytokines and the level of inflammation in the animal model. Conclusion These findings suggest that SA may be useful in the development of natural therapies for inflammatory diseases.